Relationship of ITPKA expression with the prognosis of breast cancer. Issue 4 (23rd February 2021) - Zhang, Jie; Zhang, Sujie; Li, Xiaoyan; Pi, Hongying
Abstract: Background: Breast cancer (BC) represents a most common cancer among women worldwide. The outcomes of this disease remain dismal due to frequent recurrence and metastasis. Inositol‐1, 4, 5‐trisphosphate‐3‐kinase‐A ( ITPKA ) plays an important role in regulating calcium signaling and actin dynamics. The dysregulation of ITPKA has been observed in several human cancers. The present study aimed to assess ITPKA expression and its prognostic value in BC. Methods: ITPKA expression was examined via quantitative real‐time polymerase chain reaction (qRT‐PCR) and immunohistochemistry (IHC) methods. In addition, Kaplan–Meier survival analysis and Cox regression analysis were performed to evaluate prognostic value of ITPKA in BC. Results: Upregulated ITPKA expression was found in BC samples, according to both qRT‐PCR and IHC analyses (all p < .05). ITPKA expression was positively correlated with lymph node metastasis ( p = .021) and TNM stage ( p = .009). Moreover, BC patients with high expression of ITPKA had poor overall survival compared with those with low expression (log‐rank p < .05). Cox analysis verified that ITPKA expression was an independent prognostic factor for BC patients (HR = 4.239, 95%CI = 2.221–8.093 and p = .000). Conclusion: BC cases show increased expression of ITPKA . ITPKA may act as an independent prognostic biomarker in BC. Abstract : In summary, the expression of ITPKA was elevated in tissue samples of BC and served as a potential prognostic biomarker in patients with BC. Despite we provided evidences for ITPKA as the prognostic factor in BC, the molecular mechanisms of ITPKA acts in BC needs to be further explored in the further.